Sistem Informasi Pendataan Siswa/Siswi Berbasis Web pada SMP Negeri 9 Banda Aceh - David Nataniel Rajagukguk; Rizaldi Akbar; Lukman Ahmad (Jurnal Manajemen Sistem Informasi (JMASIF), 2025)
The student data management system at SMP Negeri 9 Banda Aceh is currently still conducted manually. The process of data processing with the existing system is considered to have many shortcomings. The use of paper and Microsoft Excel in the current system makes student data prone to being lost or damaged. Therefore, the development of a web-based information system is expected to improve the speed and quality of information delivery. In this system, the main menu can only be accessed by specific users, namely the teachers. In addition to explaining the theoretical background underlying the system design, the author will also discuss the design of the web-based information system using PHP and MySQL. The design of the web-based application system will facilitate accessibility through an internet connection and improve the management of student data more effectively.